Renaissance music between science and art - Sukljan, Nejc (Muzikološki zbornik, 2020)
This paper deals with the role of ancient music theory in Gioseffo Zarlino's Istitutioni harmoniche and, within its framework, in particular with mathematical and physical considerations and their relevance to audible music. An outline of the treatise is followed by a presentation of Zarlino's justification of music as scienza and arte. Finally, two case studies are presented on joining ancient theory with contemporary musical practice: the division of the interval and the system of the senario.
Keywords: antika; Antiquity; glasbena teorija; music theory; Renaissance; renesansa; senario; Zarlino, Gioseffo